Philosophy' - After the End of Philosophy : In a Globalizing and Glocalizing World. - Chokr, Nader N. (Cambridge Scholars Publishing, 2014)
The essays included in this collection deal with a wide and diverse range of problems and issues: namely, Cultural Complexity; Globalization; Glocalization; Relativism; Embodied and Situated Cognition; Capabilities Approach; Moral Universalism; Solidarity; Cosmopolitanism; Pluralism; Human Rights; Justice; and "Philosophy" after the end of Philosophy. This work takes its main title from the last essay, in which the author makes an effort to rethink the nature and purpose of "philosophy" for the present day, sketching a proposal for a new beginning for philosophy as "critical philosophy." Such a philosophy would have a clear and compelling emancipatory thrust. At this point in human history, it would have to be underwritten by an ethical universalism that is pluralistic, historically enlightened and non-ethnocentric. In addition, it would take seriously the consequences of complexity in a world that is increasingly interconnected and interdependent, yet still so far apart, and would be prepared to draw the full implications of the embodied and situated cognition paradigm shift which has taken place in the past few decades. It would, furthermore, take aim in all of its manifestations, that is so pervasive in various quarters throughout the whole of culture and society. Finally, it would effectively contribute to the articulation and elaboration of the kinds of concepts, frameworks, narratives and practices, generally speaking, which could somehow enable humans to rise to the next level in their understanding of the globalizing and glocalizing world in which they live, and which is, as is common knowledge, dramatically confronted by a number of serious challenges, grave risks and threats, dismal shortcomings and failures. This work offers compelling analyses and diagnostics, and makes some sketch-proposals to urgently grapple with them